Gender Diversity in Corporate Governance and Top Management - Francoeur, Claude (Journal of business ethics, 2008)
This article examines whether and how the participation of women in the firm’s board of directors and senior management enhances financial performance. We use the Fama and French (1992, 1993) valuation framework to take the level of risk into consideration, when comparing firm performances, whereas previous studies used either raw stock returns or accounting ratios. Our results indicate that firms operating in complex environments do generate positive and significant abnormal returns when they have a high proportion of women officers. Although the participation of women as directors does not seem to make a difference in this regard, firms with a high proportion of women in both their management and governance systems generate enough value to keep up with normal stock-market returns. These findings tend to support the policies currently being discussed or implemented in some countries and organizations to foster the advancement of women in business.